Engineering adeno-associated virus vectors for gene therapy - Li, Chengwen; Samulski, R Jude (Nature reviews. Genetics, 2020)
Adeno-associated virus (AAV) vector-mediated gene delivery was recently approved for the treatment of inherited blindness and spinal muscular atrophy, and long-term therapeutic effects have been achieved for other rare diseases, including haemophilia and Duchenne muscular dystrophy. However, current research indicates that the genetic modification of AAV vectors may further facilitate the success of AAV gene therapy. Vector engineering can increase AAV transduction efficiency (by optimizing the transgene cassette), vector tropism (using capsid engineering) and the ability of the capsid and transgene to avoid the host immune response (by genetically modifying these components), as well as optimize the large-scale production of AAV.